A new counterterrorism strategy : why the world failed to stop Al Qaeda and ISIS/ISIL, and how to defeat terrorists /: why the world failed to stop Al Qaeda and ISIS/ISIL, and how to defeat terrorists. (2017) - Bayātī, Ḥāmid
No abstract available